Spherical boron nitride (at) ZIFs derived carbon nanotube heterostructure material and preparation method and application thereof
By growing ZIFs-derived carbon nanotubes in situ on the surface of spherical boron nitride, building a 3D thermal conductivity network, the problem of insufficient thermal conductivity of polymer-based composite materials is solved, and the improvement of high thermal conductivity and processing performance under low filler content is achieved. Keep.
Patent Information
- Application Number
- CN202411399741.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
The thermal conductivity of existing polymer-based composite materials is insufficient, and the processing and mechanical properties will decrease after adding high thermal conductivity fillers, making it difficult to meet the demands of electronic devices for high thermal conductivity, miniaturization and high integration.
By growing ZIFs-derived carbon nanotubes in situ on the spherical boron nitride surface, a 3D spherical heterostructure is constructed to form a 3D thermal conductivity network to bridge adjacent fillers, reduce interface thermal resistance, and improve the thermal conductivity of composite materials.
The high thermal conductivity performance is improved at low filler content, which enhances the thermal conductivity of composite materials, while maintaining good processing and mechanical properties.
Smart Images

Figure CN119284886A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal interface materials, and in particular relates to a spherical boron nitride-ZIFs derived carbon nanotube heterostructure material and a preparation method and application thereof. Background Art
[0002] The development trend of electronic devices towards miniaturization, high integration and high power density has placed higher requirements on the heat dissipation and heat dissipation efficiency of electronic devices. Polymer materials have good mechanical properties, chemical corrosion resistance and processability, and are lightweight and inexpensive. They are widely used in thermal management materials, but their thermal conductivity is generally less than 0.2W / (m·K), which is difficult to meet the needs of the industry. Inorganic fillers with high thermal conductivity and electrical insulation such as graphene, MgO, Al2O3, CNF and BN are usually added to improve the thermal conductivity of polymer-based composites. However, in order to achieve high thermal conductivity of composite materials, a large amount of thermally conductive fillers are usually added, but this also makes the composite materials have problems such as poor processing performance, filler agglomeration and a sharp drop in mechanical properties.
[0003] Constructing a three-dimensional thermally conductive network in a composite material has been proven to be a means to achieve high thermal conductivity at a low filler content and effectively improve the anisotropic thermal conductivity of the composite material. At the same time, adding thermally conductive fillers of different sizes, shapes or types to the polymer matrix can increase the packing density of the filler through the synergistic effect of multiple fillers, thereby improving the thermal conductivity of the composite material. However, directly blended hybrid fillers tend to form agglomerates in the polymer matrix, introducing more interfacial thermal resistance. In situ growth of other thermally conductive fillers on the surface of the thermally conductive filler to form a heterogeneous structure can effectively increase the packing density of the filler and bridge adjacent thermally conductive fillers, thereby reducing the interfacial thermal resistance of the 3D thermally conductive network to improve the thermal conductivity of the composite material.
[0004] Based on this, the present invention provides a spherical boron nitride / ZIFs-derived carbon nanotube heterostructure material and a preparation method thereof. Spherical boron nitride is obtained by simple liquid phase ultrasound, and ZIF-derived carbon nanotubes are grown in situ on its surface. A 3D thermal conductive network is constructed in a polymer matrix through a 3D spherical heterostructure and adjacent fillers are bridged to reduce the interface thermal resistance, which can effectively improve the thermal conductivity of the composite material. Summary of the invention
[0005] Technical problem: The purpose of the present invention is to provide a method for preparing spherical boron nitride / ZIFs-derived carbon nanotube heterostructure materials in order to solve the above-mentioned problems.
[0006] Technical solution: To achieve the above purpose, the technical solution adopted by the present invention is:
[0007] The first object of the present invention is to provide a spherical boron nitride @ ZIFs derived carbon nanotube heterostructure material (C-BN@ZnCo-ZCNT), wherein the C-BN@ZnCo-ZCNT heterostructure material is a spherical boron nitride (C-BN) surface on which ZIFs derived carbon nanotubes are in situ grown, and the ZIFs are metal organic framework materials formed by metal Co, Zn and 2-methylimidazole.
[0008] The present invention aims to synthesize a spherical boron nitride @ ZIFs-derived carbon nanotube heterostructure material, which can effectively improve the thermal conductivity of the composite material by constructing a 3D thermal conductive network in a polymer matrix through a 3D spherical heterostructure and bridging adjacent fillers to reduce the interfacial thermal resistance.
[0009] The second object of the present invention is to provide a method for preparing a spherical boron nitride @ ZIFs-derived carbon nanotube heterostructure material, comprising the following steps:
[0010] S1. Hexagonal boron nitride h-BN in Zn 2+ 、Co 2+ Ultrasonic treatment in metal ion solution, metal ion intercalation assisted exfoliation of h-BN to obtain spherical boron nitride C-BN,
[0011] S2, adding 2-methylimidazole in situ to the mixed solution obtained in step S1, growing ZIFs particles in situ on the surface of C-BN, and obtaining a C-BN@ZIF precursor.
[0012] S3, the C-BN@ZIF precursor is ground and mixed with melamine, and then calcined to in-situ grow ZIFs-derived carbon nanotubes on the surface of C-BN to obtain a spherical boron nitride-ZIFs-derived carbon nanotube heterostructure material C-BN@ZnCo-ZCNT.
[0013] Optionally, in some embodiments of the present invention, in step S3, the mass ratio of C-BN@ZIF to melamine is 1:(0.1-10).
[0014] Further optionally, in some embodiments of the present invention, in step S3, the mass ratio of C-BN@ZIF to melamine is 1:(0.5-5). More preferably, it is 1:(0.5-2.5). More preferably, it is 1:(1.0-2.5).
[0015] Optionally, in some embodiments of the present invention, in step S1, the amount of metal ions used is 3 to 10 mmol / gh-BN.
[0016] Further optionally, in some embodiments of the present invention, in step S1, the amount of metal ions used is 3 to 4.5 mmol / g h-BN.
[0017] Optionally, in some embodiments of the present invention, the molar ratio of the metal ion in step S1 to the 2-methylimidazole in step S2 is 1:(4-80).
[0018] Further optionally, in some embodiments of the present invention, the molar ratio of the metal ion in step S1 to the 2-methylimidazole in step S2 is 1:(2-80), and more preferably 1:(3-16).
[0019] Optionally, in some embodiments of the present invention, in step S1, the Zn 2+ 、Co 2+ Zn in metal ion solution 2 + With Co 2+ The molar ratio is (0.1~10):(10~0.1).
[0020] Further optionally, in some embodiments of the present invention, in step S1, the Zn 2+ 、Co 2+ Zn in metal ion solution 2+ With Co 2+ The molar ratio is (0.5~5):(5~0.5).
[0021] Optionally, in some embodiments of the present invention, the Zn 2+ 、Co 2+ The metal ion solution includes at least one of nitrate solution, acetate, chloride and the like.
[0022] Optionally, in some embodiments of the present invention, the Zn 2+ 、Co 2+ The solvent of the metal ion solution is a mixture of isopropanol and water, and the volume ratio of isopropanol to water is (1-10):(10-1). The preferred volume ratio of isopropanol to water is 7:3.
[0023] Optionally, in some embodiments of the present invention, in step S1, the ultrasonic power of the ultrasonic treatment is 100-300 W, and the time is 1-3 h.
[0024] Further optionally, in some embodiments of the present invention, in step S1, the ultrasonic treatment refers to 200W ultrasonic treatment for 2h.
[0025] Optionally, in some embodiments of the present invention, in step S3, the calcination is carried out under a nitrogen atmosphere at 700-900° C. for 2-5 hours, with a heating rate of 2-10° C. / min.
[0026] Further optionally, in some embodiments of the present invention, in step S3, the calcination is carried out under a nitrogen atmosphere at a temperature of 800-900°C, preferably 900°C.
[0027] The third object of the present invention is to provide an application of spherical boron nitride@ZIFs derived carbon nanotube heterostructure materials, specifically in the fields of electronic devices, thermal conductive fillers and / or thermal interface materials.
[0028] Optionally, in some embodiments of the present invention, specifically, the method for preparing the C-BN@ZIF precursor comprises the following steps:
[0029] (1) Dissolving Co(NO3)2·6H2O and Zn(NO3)2·6H2O in a mixed solvent of isopropanol and deionized water to obtain a metal ion solution, placing the solution in a centrifuge tube, adding h-BN thereto, and subjecting the solution to ultrasonic treatment by a cell crusher for a period of time to obtain C-BN;
[0030] (2) dissolving 2-methylimidazole in a mixed solvent of isopropanol and deionized water to obtain a 2-methylimidazole solution, adding the solution to the mixed solution in step (1), and continuing to ultrasonically treat the solution for a period of time using a cell crusher;
[0031] (3) The product of step (2) is centrifuged, washed, and dried to obtain C-BN@ZIF.
[0032] Optionally, in some embodiments of the present invention, the volume ratio of isopropanol to water in step (1) is (1-10):(10-1).
[0033] Optionally, in some embodiments of the present invention, the Zn 2+ With Co 2+ The molar ratio is (0.1~10):(10~0.1).
[0034] Optionally, in some embodiments of the present invention, the ultrasonic power in step (1) is 100-300 W, and the time is 1-3 h.
[0035] Optionally, in some embodiments of the present invention, the molar ratio of 2-methylimidazole to metal ions in step (2) is (4-80):1.
[0036] Optionally, in some embodiments of the present invention, the ultrasonic power in step (2) is 100-300 W, and the time is 1-3 h.
[0037] Optionally, in some embodiments of the present invention, the drying temperature in step (3) is 50 to 80° C., and the drying time is 10 to 15 hours.
[0038] Another object of the present invention is to provide the use of the spherical boron nitride@ZIFs-derived carbon nanotube heterostructure material (C-BN@ZnCo-ZCNT heterostructure material) in electronic devices, thermal conductive fillers or thermal interface materials.
[0039] Another object of the present invention is to provide a thermally conductive composite material, wherein the thermally conductive composite material is loaded with 5 wt% h-BN and 0.5-2.5 wt% C-BN@ZnCo-ZCNT.
[0040] Optionally, in some embodiments of the present invention, the thermally conductive composite material uses PA as a polymer matrix.
[0041] Optionally, in some embodiments of the present invention, the thermally conductive composite material is further loaded with a photoinitiator.
[0042] Optionally, in some embodiments of the present invention, the thermal conductivity of the thermally conductive composite material is higher than 0.35 W·m-1·K-1.
[0043] Optionally, in some embodiments of the present invention, the thermal conductivity of the thermally conductive composite material is up to 0.79 W·m-1·K-1.
[0044] Optionally, in some embodiments of the present invention, the thermal conductivity of the thermally conductive composite material is 0.35-0.8 W·m-1·K-1.
[0045] Another object of the present invention is to provide use of the thermally conductive composite material in electronic devices, thermally conductive fillers or thermal interface materials.
[0046] Beneficial effects: The present invention has at least the following advantages:
[0047] (1) The present invention can obtain spherical boron nitride from sheet-like h-BN by simple ultrasonic treatment;
[0048] (2) The 3D spherical boron nitride@ZIFs-derived carbon nanotube heterostructure material obtained by in situ growth of ZIFs-derived carbon nanotubes on the surface of spherical boron nitride can construct a 3D thermal conductive network in a polymer matrix, and bridge adjacent fillers by ZIFs particles and carbon nanotubes to reduce interfacial thermal resistance, effectively improve the thermal conductivity of the composite material, prepare an isotropic thermal conductive composite material, and achieve high thermal conductivity at a low filler content.
[0049] (3) The materials used in the present invention are cheap and readily available, and the preparation process is easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1Schematic diagram of the synthesis process of C-BN@ZnCo-ZCNT and the preparation and two-stage curing process of the composite material.
[0051] Figure 2 These are scanning electron microscope photographs of (a) original h-BN, (b) comparative example 1, (c) example 4 before carbonization, (d) comparative example 2, (e) comparative example 3, (f) comparative example 4, (g) example 1, (h) example 2, (i) example 3, (j) example 4, and (k) example 5.
[0052] Figure 3 SEM images of (a) C-BN@Co-ZCNT, (b) C-BN@Zn-ZCNT, and (c) C-BN@ZnCo-ZCNT.
[0053] Figure 4 SEM images of (a, b) C-BN@ZnCo-ZCNT-6 (700℃), (c) C-BN@ZnCo-ZCNT-7 (800℃) and (d) C-BN@ZnCo-ZCNT-4 (900℃), (e) Raman spectrum of C-BN@ZnCo-ZCNT-2 calcined at different temperatures, and (f) TGA curve of C-BN@ZnCo-ZCNT-4 (900℃) in O2 atmosphere.
[0054] Figure 5 (a) XRD spectra of h-BN, C-BN@ZnCo-ZIF, C-BN@ZnCo-ZCNT-6, C-BN@ZnCo-ZCNT-7 and C-BN@ZnCo-ZCNT-4 and (b, c) the corresponding enlarged XRD spectra.
[0055] Figure 6 (a) Infrared spectra of h-BN, C-BN@ZnCo-ZIF and C-BN@ZnCo-ZCNT-4, (b) full XPS spectra of h-BN, C-BN@ZnCo-ZIF and C-BN@ZnCo-ZCNT-4, (c) Zn 2p, (d) Co 2p, (e) C 1s and (f) N 1s spectra of C-BN@ZnCo-ZCNT-4.
[0056] Figure 7 (a) PA-S, (b) H 5.0 / PA-S、(c)H 5.0 C 0.5 / PA-S, (d)H 5.0 C 1.0 / PA-S、(e)H 5.0 C 1.5 / PA-S、(f)H 5.0 C2.0 / PA-S、(g,h)H 5.0 C 2.5 SEM image of the cross section of / PA-S composite material.
[0057] Figure 8 (a) Thermal conductivity of different composite materials and (b) thermal conductivity enhancement rate.
[0058] Fig. 9 (a)H 5.0 / PA-S and (b)H 5.0 C w Schematic diagram of heat conduction of / PA-S composite material.
[0059] Fig.10 For (a) PA-S and H 5.0 C 2.5 Infrared thermal imaging of the PA-S / PA-S composite placed on a heating table, (b) PA-S and H 5.0 C 2.5 (a) Curve of the surface temperature of the / PA-S composite material changing with time, (c) Schematic diagram of the heat dissipation device.
[0060] Fig.11 TGA curves of different composite materials. DETAILED DESCRIPTION
[0061] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but it does not constitute a limitation of the present invention. According to the following examples, the present invention can be better understood. However, it is easy for those skilled in the art to understand that the specific material ratios, process conditions and results described in the embodiments are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.
[0062] The present invention relates to a boron nitride heterostructure material and a preparation method thereof, in particular to a spherical boron nitride@metal organic framework derived carbon nanotube heterostructure material, wherein the preparation method comprises: firstly, hexagonal boron nitride (h-BN) is reacted with Zn 2+ 、Co 2+After ultrasonic treatment in a metal ion solution for a period of time, the h-BN is exfoliated with the aid of metal ion intercalation, and the obtained h-BN nanosheets curl spontaneously and assemble into spherical boron nitride (C-BN), and then 2-methylimidazole is added to the mixed solution to in-situ grow MOFs particles (ZIF) on the surface of C-BN to obtain C-BN@ZIF precursor; after physical grinding and mixing with melamine, ZIF carbonization-derived carbon nanotubes are in-situ grown on the surface of C-BN after high-temperature calcination to obtain spherical boron nitride-ZIF-derived carbon nanotube heterostructure materials (C-BN@ZCNT). The spherical nanofiller preparation process of the present invention has the advantages of being simple and easy, cheap and easy to obtain raw materials, and easy to operate. This spherical boron nitride@carbon nanotube heterogeneous material is used as a thermally conductive filler, which is easy to form a three-dimensional thermally conductive network in the composite material, and bridges adjacent fillers through carbon nanotubes to reduce the interface thermal resistance, and has good application prospects in thermal interface materials.
[0063] The synthesis process of spherical boron nitride / ZIFs-derived carbon nanotube heterostructures (C-BN@ZnCo-ZCNT), preparation and curing of composite materials are shown in Figure 2. Figure 1 As shown. First, through ultrasonic treatment, the block h-BN begins to peel off from the edge, so that the h-BN edge layer opens, and the thin sheet curls naturally, and the partially curled thin sheet self-assembles into spherical boron nitride (C-BN). Then, a metal ion solution (Co 2+ and Zn 2+ ), intercalated into the interlayer of h-BN under ultrasonic action, weakening the interlayer van der Waals interaction, and at the same time a large number of metal ions were adsorbed on the surface of C-BN and BNNS. Next, 2-methylimidazole was introduced to allow the in-situ assembly of ZIFs particles with Co and Zn as metal centers on the surface of C-BN to form a heterostructure precursor (C-BN@ZnCo-ZIF). Subsequently, C-BN@ZnCo-ZIF was ground and mixed with melamine, and then calcined at high temperature under N2 atmosphere. The metal cations were reduced to metal nanoparticles, which acted as catalysts to promote the growth of carbon nanotubes. The nitrogen atoms in melamine can provide electrons to the metal ions, reducing them to metal nanocatalysts, thereby promoting the formation of carbon nanotubes
[133] . Finally, carbon nanotubes were in-situ grown on the surface of C-BN to form a spherical boron nitride / ZIFs-derived carbon nanotube heterostructure (C-BN@ZnCo-ZCNT). These in-situ grown carbon nanotubes can bridge adjacent fillers, reduce interfacial thermal resistance, and promote heat conduction. C-BN@ZnCo-ZCNT and polymer are formulated into ink suitable for DIW printing to prepare a thermally conductive composite material with a three-dimensional thermal conductive network.
[0064] The present invention provides a spherical boron nitride-ZIFs-derived carbon nanotube heterostructure material (C-BN@ZCNT), belonging to the field of energy and thermal interface materials. The present invention in situ grows ZIF-derived carbon nanotubes on the surface of C-BN to obtain a spherical boron nitride-MOFs-derived carbon nanotube heterostructure material (C-BN@ZCNT). The spherical nanofiller of the present invention has the advantages of simple and easy preparation process, cheap and readily available raw materials, easy operation, etc.
[0065] The raw materials used in this example are all commercially available.
[0066] Example 1: C-BN@ZnCo-ZCNT-1, wherein the mass ratio of C-BN@ZnCo-ZIF to melamine is 1:0.5.
[0067] (1) 0.65 g (2.25 mmol) Co(NO3)2·6H2O and 0.67 g (2.25 mmol) Zn(NO3)2·6H2O were completely dissolved in 15 mL of a mixed solvent of isopropanol and deionized water (V(isopropanol):V(H2O)=7:3), 0.1 g h-BN was dispersed into the above solution and placed in a centrifuge tube, and then ultrasonically treated at 200 W for 2 h in a cell crusher to obtain a C-BN system;
[0068] (2) 18 mmol (1.48 g) of 2-methylimidazole was completely dissolved in 5 mL of a mixed solvent of isopropanol and deionized water (V (isopropanol): V (H2O) = 7:3), added in situ to the C-BN system described in step (1), and continued to be ultrasonically treated in a cell crusher at 200 W for 1 h, centrifuged, washed with deionized water 3 times, washed with anhydrous ethanol 2 times, and dried at 70 ° C for 24 hours to obtain the precursor C-BN@ZnCo-ZIF-1;
[0069] (3) 0.1 g C-BN@ZnCo-ZIF-1 and 0.05 g melamine were ground and mixed in a mortar, and then sent into a tubular furnace for calcination. Under a nitrogen atmosphere, the temperature was set to rise from room temperature to 900 °C at a heating rate of 5 °C / min, and kept at this temperature for 3 h. After naturally cooling to room temperature, the mixture was taken out to finally obtain C-BN@ZnCo-ZCNT-1.
[0070] The obtained heterostructure material C-BN@ZnCo-ZCNT-1 scanning electron microscope photo is shown in Figure 2 (g) is shown, and the specific result analysis is detailed in the subsequent example result analysis.
[0071] Example 2: C-BN@ZnCo-ZCNT-2, wherein the mass ratio of C-BN@ZnCo-ZIF to melamine is 1:1.
[0072] The experiment was carried out with 0.1 g of C-BN@ZnCo-ZIF-2 and 0.1 g of melamine, and the rest was the same as in Example 1, to obtain C-BN@ZnCo-ZCNT-2.
[0073] The obtained heterostructure material C-BN@ZnCo-ZCNT-2 scanning electron microscope photo is shown in Figure 2 (h) is shown, and the specific result analysis is detailed in the subsequent example result analysis.
[0074] Example 3: C-BN@ZnCo-ZCNT-3, wherein the mass ratio of C-BN@ZnCo-ZIF to melamine is 1:1.5.
[0075] The experiment was carried out with 0.1 g of C-BN@ZnCo-ZIF-3 and 0.15 g of melamine, and the rest was the same as in Example 1, to obtain C-BN@ZnCo-ZCNT-3.
[0076] The obtained heterostructure material C-BN@ZnCo-ZCNT-3 scanning electron microscope photo is shown in Figure 2 (i) is shown, and the specific result analysis is detailed in the subsequent example result analysis.
[0077] Example 4: C-BN@ZnCo-ZCNT-4, wherein the mass ratio of C-BN@ZnCo-ZIF to melamine is 1:2.
[0078] The experiment was carried out with 0.1 g of C-BN@ZnCo-ZIF-4 and 0.2 g of melamine, and the rest was the same as in Example 1, to obtain C-BN@ZnCo-ZCNT-4.
[0079] The obtained heterostructure carbonization precursor C-BN@ZnCo-ZIF-4 scanning electron microscope photo is shown in Figure 2 (c) shows the SEM photo of the obtained heterostructure material C-BN@ZnCo-ZCNT-4. Figure 2 (j), for detailed analysis of the results, please refer to the subsequent example result analysis.
[0080] Example 5: C-BN@ZnCo-ZCNT-5, wherein the mass ratio of C-BN@ZnCo-ZIF to melamine is 1:2.5.
[0081] The experiment was carried out with 0.1 g of C-BN@ZnCo-ZIF-5 and 0.25 g of melamine, and the rest was the same as in Example 1, to obtain C-BN@ZnCo-ZCNT-5.
[0082] The scanning electron microscope photo of the obtained heterostructure material C-BN@ZnCo-ZCNT-5 is shown in Figure 2(k) is shown, and the specific result analysis is detailed in the subsequent example result analysis.
[0083] Example 6: C-BN@ZnCo-ZCNT-6, wherein the carbonization temperature is 700°C
[0084] The experiment was carried out at a carbonization temperature of 700°C, with the rest being the same as in Example 4, to obtain C-BN@ZnCo-ZCNT-6.
[0085] The obtained heterostructure material C-BN@ZnCo-ZCNT-6 scanning electron microscope photo is shown in Figure 4 As shown in (a, b), the Raman spectra are Figure 4 (e) is shown, and the specific result analysis is detailed in the subsequent example result analysis.
[0086] Example 7: C-BN@ZnCo-ZCNT-7, wherein the carbonization temperature is 800°C
[0087] The experiment was carried out at a carbonization temperature of 800°C, with the rest being the same as in Example 4, to obtain C-BN@ZnCo-ZCNT-7.
[0088] The scanning electron microscope photo of the obtained heterostructure material C-BN@ZnCo-ZCNT-7 is shown in Figure 4 (c) shows the Raman spectrum. Figure 4 (e) is shown, and the specific result analysis is detailed in the subsequent example result analysis.
[0089] Comparative Example 1: C-BN
[0090] 2.25mmol Co(NO3)2·6H2O and 2.25mmol Zn(NO3)2·6H2O were completely dissolved in 15mL of a mixed solvent of isopropanol and deionized water (V(isopropanol):V(H2O)=7:3), 0.1g h-BN was dispersed into the above solution and placed in a centrifuge tube, and then ultrasonically treated at 200W for 2h in a cell crusher to obtain a C-BN system. The system was centrifuged, washed with deionized water 3 times, washed with anhydrous ethanol twice, and dried at 80°C for 12 hours to obtain C-BN.
[0091] The obtained material C-BN scanning electron microscope photo is as follows Figure 2 (b), for detailed analysis of the results, please refer to the subsequent example result analysis.
[0092] Comparative Example 2: C-BN@ZnCo-ZCNT-0, wherein the mass ratio of C-BN@ZnCo-ZIF to melamine is 1:0.
[0093] The experiment was carried out with 0.1 g of C-BN@ZnCo-ZIF and 0 g of melamine, and the rest was the same as in Example 1, to obtain C-BN@ZnCo-ZCNT-0.
[0094] The scanning electron microscope photo of the obtained heterostructure material C-BN@ZnCo-ZCNT-0 is shown in Figure 2 (d) is shown, and the specific result analysis is detailed in the subsequent example result analysis.
[0095] Comparative Example 3: C-BN@Co-ZCNT
[0096] (1) 1.3 g (4.5 mmol) Co(NO3)2·6H2O was dissolved in 15 mL of a mixed solvent of isopropanol and deionized water (V(isopropanol):V(H2O)=7:3), 0.1 g h-BN was dispersed into the above solution and placed in a centrifuge tube, and then ultrasonically treated at 200 W for 2 h in a cell crusher to obtain a C-BN system; the rest of the process was the same as in Example 4 to obtain C-BN@Co-ZCNT.
[0097] The obtained heterostructure material C-BN@Co-ZCNT scanning electron microscope photo is shown in Figure 2 (e) is shown, and the specific result analysis is detailed in the subsequent example result analysis.
[0098] Comparative Example 4: C-BN@Zn-ZCNT
[0099] (1) 1.34 g (4.5 mmol) Zn(NO3)2·6H2O was dissolved in 15 mL of a mixed solvent of isopropanol and deionized water (V(isopropanol):V(H2O)=7:3), 0.1 g h-BN was dispersed into the above solution and placed in a centrifuge tube, and then ultrasonically treated at 200 W for 2 h in a cell crusher to obtain a C-BN system; the rest of the process was the same as in Example 1 to obtain C-BN@Zn-ZCNT.
[0100] The obtained heterostructure material C-BN@Zn-ZCNT scanning electron microscope photo is shown in Figure 2 (f) is shown, and the specific result analysis is detailed in the subsequent example result analysis.
[0101] Example result analysis:
[0102] The products of Comparative Examples 1-4 before carbonization and Examples 1-5 were tested by scanning electron microscopy.
[0103] First, Figure 2 The scanning electron microscope photograph shows that Figure 2 (a) is a scanning electron microscope image of the original h-BN. The h-BN is a two-dimensional sheet structure with a lateral size of about 20-30 μm and a relatively thick thickness. Figure 2The product C-BN obtained in Comparative Example 1 shown in (b) is spherical boron nitride with a diameter of about 8-15 μm. Under liquid phase ultrasound conditions, due to the decrease in surface tension, the edge of h-BN curls inward to form spherical boron nitride; Figure 2 The product obtained in Example 4 shown in (c) is a heterogeneous carbonized precursor, and the CoZn-ZIF particles are relatively evenly coated on the C-BN surface due to in-situ growth, which is conducive to the in-situ growth of carbon nanotubes; Figure 2 Comparative Example 2 shown in (d) is a heterostructure material obtained by directly carbonizing the precursor C-BN-CoZn without adding melamine. Direct carbonization is performed without adding melamine, and no carbon nanotubes are generated on the surface of C-BN; Figure 2 (e) Comparative Example 3 and Figure 2 The product obtained in Comparative Example 4 shown in (f) is carbon nanotubes catalyzed by ZIF with a single metal as the metal center on the C-BN surface. Figure 2 (e) The number of carbon nanotubes on the surface of Comparative Example 3 is shown as Figure 2 (f) shows more comparative example 4, indicating that the effect of Co catalyzing carbon nanotubes is worse than that of Zn, but not as good as that of bimetallic catalyzing carbon nanotubes (Example 4, Figure 2 (c)).
[0104] Second, according to the research results of Comparative Example 2, it is shown that melamine has a significant effect on the growth of carbon nanotubes (CNTs), especially in the development of thermally conductive composite materials. In the absence of melamine, the C-BN@ZnCo-ZIF precursor can only generate calcined ZIFs particles with rough and concave surfaces, but no carbon nanotubes are generated. This shows that in the absence of a suitable catalyst, the matrix cannot effectively promote the formation of carbon nanotubes. By adding melamine, its abundant nitrogen atoms can act as electron donors during the pyrolysis process to help reduce metal ions into metal nanoparticles, which act as catalysts to promote the growth of carbon nanotubes. This method of successfully introducing carbon nanotubes into materials is crucial to improving the thermal conductivity of composite materials because carbon nanotubes have excellent thermal and electrical conductivity. The results further pointed out that, Figure 2In the examples 1-5 shown in (g), (h), (i), (j), and (k), the number of carbon nanotubes increases as the amount of melamine added gradually increases, mainly because melamine is rich in nitrogen atoms, which can coordinate with metal salts to effectively anchor single metal atoms. Through pyrolysis under high temperature conditions, nitrogen atoms can provide electrons to metal ions, reducing them to metal nanocatalysts, thereby promoting the formation of carbon nanotubes. In particular, when the mass ratio of C-BN-ZIF to melamine in Example 4 is 1:2, the number of carbon nanotubes generated is the largest and the length is the longest, and the resulting spherical heterostructure material is in the most ideal state. The spherical heterostructure is conducive to building a 3D thermal conductive network in a polymer matrix, and the longer carbon nanotubes can better bridge adjacent fillers with ZIFs particles to reduce interface thermal resistance, thereby further improving the thermal conductivity of the composite material. Such longer carbon nanotubes can better bridge adjacent thermal conductive fillers, reduce interface thermal resistance, and thus further improve the overall thermal conductivity of the composite material. The construction of this three-dimensional thermally conductive network will be very beneficial for practical applications such as electronic device heat dissipation, high-performance batteries and other fields that require excellent thermal conductivity. Therefore, the present study reveals the optimization of carbon nanotube growth in carbon-based and metal organic framework (MOF)-derived materials by adding melamine, which not only promotes the efficient synthesis of carbon nanotubes, but also provides an effective way to prepare high thermal conductivity composite materials.
[0105] Third, the effect of metal active centers in the generation process of carbon nanotubes (CNTs) was studied according to Comparative Examples 3 and 4. Figure 3 (a) and (b) show the heterostructured CNTs generated on C-BN support using only Co or Zn as the single metal center. The observation results show that the number of CNTs on the C-BN@Co-ZCNT sample is greater than that on the C-BN@Zn-ZCNT, indicating that Co's promotion of CNTs generation exceeds that of Zn. The growth density of CNTs under these two single metal catalysis did not reach that of C-BN@ZnCo-ZCNT ( Figure 3 (c)), while the latter exhibits better catalytic efficiency due to its bimetallic synergistic effect.
[0106] Fourth, the effect of carbonization temperature on the growth characteristics of carbon nanotubes was studied according to Examples 4, 6, and 7, especially the pyrolysis process of the precursor C-BN@ZnCo-ZIF at different temperatures. The study found that with the increase of carbonization temperature, the morphology and graphitization degree of carbon nanotubes changed significantly, and these changes directly affected their function in constructing a thermal conductive network. Specifically, Figure 4ad shows that the precursor C-BN@ZnCo-ZIF calcined at 700℃ produces a small number of carbon nanotubes with limited length, making it difficult to form an effective bridge connection. When the temperature is raised to 800℃, the number of carbon nanotubes generated increases and the length is extended; when further raised to 900℃, not only the number increases significantly, but the increase in length is more conducive to achieving effective bridging between different materials.
[0107] Fifth, in Raman spectroscopy analysis, the carbon nanotubes grown in situ on the surface make the heterostructure material have a Raman spectrum of 1340 cm -1 The D band at 1570 cm-1 (representing defective carbon) and -1 The G band (representing graphitized carbon) shows obvious characteristic peaks. This indicates that a carbon tube structure with a certain level of graphitization is formed in situ. The intensity ratio of the D band and the G band (ID / IG) is an indicator for judging the degree of graphitization of carbon materials. The lower the ID / IG ratio, the fewer defects, the more perfect the structure, and the higher the level of graphitization; this is very beneficial in improving the thermal conductivity of carbon nanotubes. From the data, it can be seen that the ID / IG ratios of C-BN@ZnCo-ZCNT-6 (700℃) (corresponding to C-BN@ZnCo-ZCNT-2-700 in the figure), C-BN@ZnCo-ZCNT-7 (800℃) (corresponding to C-BN@ZnCo-ZCNT-2-800 in the figure) and C-BN@ZnCo-ZCNT-4 (900℃) (corresponding to C-BN@ZnCo-ZCNT-2-900 in the figure) samples are 1.35, 1.28 and 1.18, respectively, indicating that with the increase of heat treatment temperature, the graphitization level increases accordingly. In particular, at a carbonization temperature of 900℃, the carbon nanotubes on the surface of C-BN are not only numerous and long, but also have a more perfect lattice structure, which helps them to be used as connecting materials and improve the thermal conductivity of composite materials. Figure 4 The results of thermal gravimetric analysis in Figure f show that after treatment at 800°C in air, the filler residue in the C-BN@ZnCo-ZCNT-4 (900°C) sample accounts for 71.97%, which further confirms its high carbon content. Carbon nanotubes with high carbon content can effectively connect adjacent fillers, thereby reducing interfacial thermal resistance and improving the overall thermal conductivity of the composite material.
[0108] Sixth, the lattice structure of the heterostructured materials was analyzed by X-ray diffraction (XRD) technique, such as Figure 5ac revealed that after high-temperature carbonization treatment, the original characteristic peaks of C-BN@ZnCo-ZIF disappeared, and new characteristic peaks appeared with different carbonization temperatures. This shows that C-BN@ZnCo-ZIF was transformed into C-BN / carbon-based heterostructure materials through high-temperature treatment. The original h-BN sample showed diffraction peaks corresponding to (002), (100), (011), (012), and (004) crystal planes at 27.27°, 42.16°, 44.40°, 50.72°, and 55.62°. For C-BN@ZnCo-ZCNT-6 (700℃), C-BN@ZnCo-ZCNT-7 (800℃) and C-BN@ZnCo-ZCNT-4 (900℃), their (002) crystal plane diffraction peaks are located at 27.19°, 27.15° and 27.11°, respectively, indicating the presence of h-BN, graphitic carbon and g-C3N4. Compared with the original h-BN, the (002) peak intensity of these heterostructures is reduced and shifts to a lower angle with the increase of carbonization temperature. This phenomenon indicates that the interlayer spacing of h-BN increases and the high temperature treatment promotes its exfoliation. In addition, all samples show the (111) and (200) crystal plane diffraction peaks of metallic cobalt at 44.61° and 51.86°. In particular, C-BN@ZnCo-ZCNT-2-700 presents a ZnO (102) crystal plane diffraction peak at 48.86°; however, when the carbonization temperature exceeds 800 °C, the characteristic peak associated with ZnO becomes difficult to detect, because ZnO may be reduced to metallic Zn and volatilize at temperatures above 800 °C.
[0109] Seventh, Fourier transform infrared spectroscopy (FT-IR) is used to analyze the chemical composition of heterostructured materials in detail, such as Figure 6 As shown in a. During the transformation of the C-BN@ZnCo-ZIF precursor, the characteristic peaks of the original ZIFs particles no longer exist after carbonization. h-BN and its carbonization product C-BN@ZnCo-ZCNT-2-900 have a peak at 815 cm -1 and 1372cm -1 Two distinctive absorption peaks are shown at each location, which correspond to the out-of-plane bending of the BNB bond and the in-plane stretching vibration of the BN bond. No new absorption peaks were found in the C-BN@ZnCo-ZCNT-2-900 sample obtained in Example 4, which shows that the heterostructure material does not contain other organic components.
[0110] The elemental composition and chemical state of the heterostructured materials were further analyzed using X-ray photoelectron spectroscopy (XPS). Table 1 lists the element content ratios of h-BN, C-BN@ZnCo-ZIF, and C-BN@ZnCo-ZCNT-4. Figure 6The full XPS spectrum shown in b reveals that the original h-BN contains only B, N, C and O elements. Compared with h-BN, the characteristic signals of Zn and Co elements were introduced into the C-BN@ZnCo-ZIF precursor. In the final high-temperature calcined product C-BN@ZnCo-ZCNT-2-900 of Example 4, only the signals of B, N, C, O and Co elements were detected, and the characteristic signal of Zn disappeared, which indicates that ZnO was reduced and released as metallic Zn under high-temperature treatment at 900°C, which is consistent with the XRD results and the Zn 2p peak fitting results of C-BN@ZnCo-ZCNT-2-900 (see Figure 6 c) conform to. Figure 6 The peak shape fitting of Co 2p in C-BN@ZnCo-ZCNT-4 shown in d shows that the peaks at 781.5 and 797.4 eV represent Co 2+ state, the peaks at 779.9 and 795.6 eV represent Co 3+ state, while the peaks at 785.9 and 803.7 eV are satellite peaks. C 1s peak shape fitting results ( Figure 6 e) shows that the C content in the C-BN@ZnCo-ZCNT-4 sample is significantly increased compared to the original h-BN, indicating the formation of a carbon-based heterostructure. The characteristic peaks at 284.5, 285.1, 286.0 and 289.0 eV correspond to CC / C=C, CN, CO and OC=O, respectively. The characteristic peak of C=C reveals the presence of graphitic carbon, indicating the successful synthesis of graphitized carbon nanotubes, which may help improve the thermal conductivity of the material. The peak of CN may come from g-C3N4 formed at high temperature. Figure 6 f shows the fitting results of the N1s peak in C-BN@ZnCo-ZCNT-4. The peaks at 398.2, 398.5, 398.8, 399.3, and 401.1 eV are respectively assigned to NB, pyridinic nitrogen, metal (Co)-N x The presence of coordinated, pyrrolic and graphitic nitrogen.
[0111] Table 1 XPS element content analysis of h-BN, C-BN@ZnCo-ZIF and C-BN@ZnCo-ZCNT-4
[0112]
[0113] Application example: Preparation of C-BN@ZnCo-ZCNT composite materials
[0114] The phenolic phthalonitrile resin and the photocurable 4-acryloylmorpholine (ACMO) were dissolved in a mass ratio of 7:4, denoted as PN. PN and photocurable modified phenolic epoxy acrylate (EA) were prepared in a ratio of 7:3 to form a polymer matrix (PA). Then, 6wt% of fumed silica was added to the polymer matrix to adjust its rheological properties to obtain PA-S. Subsequently, h-BN (5wt% of the ink), different contents of C-BN@ZnCo-ZCNT-2 (0.5, 1, 1.5, 2, 2.5wt% of the ink), and a photoinitiator (1173, 2wt% of the photocurable resin) were added, and the mixture was placed in a ball mill and mixed evenly by a high-speed disperser to prepare an ink for DIW printing.
[0115] Before DIW printing, the ink is first subjected to centrifugal defoaming treatment. Then the treated ink is loaded into a syringe and installed in a homemade DIW 3D printer for printing. After printing, the sample needs to be cured under UV light, and then cured at a certain temperature and time (100℃ for 2h, 150℃ for 2h, 180℃ for 2h, 200℃ for 2h, 250℃ for 4h, 280℃ for 2h, 315℃ for 2h), and finally H5.0 / PA-S and H5.0Cw / PA-S composite materials are obtained. Among them, w represents the percentage of C-BN@ZnCo-ZCNT-2, and the values are 0.5, 1, 1.5, 2, and 2.5 respectively.
[0116] PA-S, H5.0 / PA-S and H5.0Cw / PA-S composites were obtained by DIW printing and two-stage curing, and their fracture cross-sectional morphologies were observed by scanning electron microscopy. Figure 7 In a, the cross section of pure resin PA is dense and smooth. Figure 7 As can be seen in b, a large number of h-BN sheets are exposed in the cross section of the H5.0 / PA-S composite material, and these flaky materials are oriented along the printing direction. This is mainly because during the printing process, the nozzle will generate a certain shear stress, causing the h-BN sheets with a larger aspect ratio to tend to be oriented along the flow direction, that is, the printing direction, thereby reducing the flow resistance and forming oriented h-BN sheets, which is helpful to build a thermal conductive network and improve the thermal conductivity of the composite material. However, due to the low content of h-BN, the connection between h-BN is still not tight enough to form an effective heat conduction path. Adding a small amount of heterogeneous structure filler C-BN@ZnCo-ZCNT-2-900 can serve as a bridge to connect adjacent h-BN sheets (see Figure 7 ch), forming a more continuous and dense thermal conductive network in the composite material, which is expected to further improve the thermal conductivity of the composite material.
[0117] according to Figure 8 Based on the test results in a, we studied the effect of heterogeneous structural materials on the thermal conductivity of composite materials and calculated the thermal conductivity enhancement efficiency using formula 3-1. The results are shown in Figure 8 b. The thermal conductivity of pure PA-S is 0.15 W·m -1 ·K -1 When 5wt% h-BN is added, the thermal conductivity of the H5.0 / PA-S composite material reaches 0.34W·m -1 ·K -1 , increased by 126.7%. The addition of fillers effectively improves the thermal conductivity of the composite material. h-BN forms an effective thermal conductive network in the polymer matrix, which is affected by the extrusion shear force and promotes the thermal conductivity of the composite material. With the increase of the content of the heterogeneous structure material C-BN@ZnCo-ZCNT-2-900, the thermal conductivity of the composite material is further improved. The thermal conductivity of H5.0C0.5 / PA-S, H5.0C1.0 / PA-S, H5.0C1.5 / PA-S, H5.0C2.0 / PA-S, and H5.0C2.5 / PA-S composite materials are 0.38, 0.48, 0.51, 0.69, and 0.79 W·m, respectively. -1 ·K -1There are two main reasons for the improvement of thermal conductivity: (1) The increase in filler content makes the thermal network formed by DIW printing more compact, reduces phonon scattering, promotes heat conduction, and effectively improves the thermal conductivity of the composite material; (2) At this time, the filler forming the thermal network is a multi-level hybrid filler. On the one hand, the spherical heterostructure material C-BN@ZnCo-ZCNT-2-900 can bridge adjacent sheet-like h-BN, increase the contact between fillers to form a three-dimensional thermal network, and at the same time, the microscopic contact of the carbon nanotubes in situ grown on the surface of a single C-BN@ZnCo-ZCNT-2-900 can achieve a more effective bridging effect, thereby forming a more effective and continuous thermal network, reducing the interfacial thermal resistance and promoting heat transfer. On the other hand, the BNNS obtained by exfoliation and the g-C3N4 formed by calcining melamine can be used as small-sized fillers to fill the gaps between large-sized fillers, forming a denser thermal network, reducing phonon scattering, and thus improving the thermal conductivity of the composite material. Compared with PA-S, the thermal conductivity of H5.0C0.5 / PA-S, H5.0C1.0 / PA-S, H5.0C1.5 / PA-S, H5.0C2.0 / PA-S, and H5.0C2.5 / PA-S composites increased by 153.3%, 220.0%, 240.0%, 360.0%, and 426.7%, respectively. The above results show that when the addition amount of C-BN@ZnCo-ZCNT-2-900 is 2wt%, under the action of multi-level mixed fillers, a relatively complete thermal conductive network is formed in the composite material, and the thermal conductivity of the composite material is greatly increased. When the content of C-BN@ZnCo-ZCNT-2-900 is further increased, the thermal conductivity of the composite material will be further improved, but the substantial increase in the content of hybrid fillers will greatly reduce the printability and photocuring performance of the composite material.
[0118] In the description of the improvement of thermal conductivity of composite materials, we further explained the thermal conductivity mechanism. In the H5.0 / PA-S composite material, the flake h-BN is subjected to the shear stress at the nozzle during DIW printing, and tends to be oriented along the extrusion direction to reduce flow resistance, forming an oriented thermal conductive network (see Fig. 9 a). However, due to the low filler content, the fillers are dispersed in isolation in the matrix, and there are many gaps between the fillers, which cannot form a continuous thermal conductive network, limiting the improvement of the thermal conductivity of the composite material. On the contrary, the addition of the heterogeneous structure material C-BN@ZnCo-ZCNT-2-900 rapidly improves the thermal conductivity of the composite material at a lower filling amount. Fig. 9As shown in (b), the spherical C-BN@ZnCo-ZCNT-2-900 can bridge adjacent h-BN to form an efficient three-dimensional thermal conductive network, while the carbon nanotubes grown in situ on its surface increase the contact sites. In addition, the small-sized BNNS and g-C3N4 significantly increase the filler filling density, reduce the interfacial thermal resistance, and reduce phonon scattering. Therefore, under the synergistic effect of multi-level hybrid fillers, an efficient and continuous three-dimensional thermal conductive network is formed in the composite material, which greatly improves the thermal conductivity of the composite material.
[0119] We further tested the heat dissipation performance of the prepared composite materials. PA-S and H5.0C2.5 / PA-S composite materials were placed on a heating table, heated from 25°C for 120 seconds, and the temperature changes on their surfaces were observed using an infrared thermal imager (see Fig.10 a). After heating for 120s, the temperature of the hot plate was about 73℃, while the surface temperatures of PA-S and H5.0C2.5 / PA-S composites were 68.8℃ and 63.6℃, respectively. Compared with PA-S, the surface equilibrium temperature of H5.0C2.5 / PA-S decreased by 5.2℃, indicating that the H5.0C2.5 / PA-S composite prepared by 3D printing has better heat dissipation performance, which is mainly attributed to the dense three-dimensional thermal conductive network formed by the hybrid filler. Therefore, H5.0C2.5 / PA-S composites show good application prospects in the field of thermal management as thermal conductive materials.
[0120] Fig.11 The TGA curves of EA, PA-S, H5.0 / PA-S and H5.0Cw / PA-S composites are shown, and Table 2 lists the decomposition temperatures (T 5% 、T 10% ) and the percentage of residual matter after thermal weight loss at 800℃ (Y c 800). The results show that the addition of PN resin and filler significantly improves the thermal stability of the composite material. The T5% and T10% of pure EA resin are 390.1℃ and 399.0℃ respectively, and the residual carbon rate after thermal weight loss at 800℃ is only 14.3%. When PN resin is introduced, the thermal stability of the two-component resin is significantly improved, and the T 5% and T 10% The temperature of the PN resin increased to 406.6℃ and 427.7℃ respectively, and the residual carbon rate increased to 65.9%. This improvement is mainly attributed to the high thermal stability and high residual carbon rate of the PN resin. During the thermal curing process, the polymer chain of the PN resin forms a heterocyclic macromolecular structure with a high cross-linking density, which significantly improves the thermal stability of the resin. At the same time, the high aromatic structure content also gives the material a higher residual carbon rate.
[0121] In addition, the introduction of fillers further enhances the thermal stability of the composites. 5% and T 10% The h-BN acts as a physical barrier dispersed in the resin matrix, restricting the movement of molecular chains. Finally, the T 5% and T 10% The temperatures reach 413.4℃ and 441.7℃ respectively, and the residual carbon rate can reach 71.0%.
[0122] Table 2 Decomposition temperature (T) of different composite materials at 5wt% and 10wt% weight loss 5% 、T 10% ) and the percentage of residual material after thermal weight loss at 800℃ (Y c 800)
[0123]
[0124] In summary, the present invention obtains spherical boron nitride by simple liquid phase ultrasound, grows ZIF particles in situ on its surface, and grows carbon nanotubes in situ on the C-BN surface by high-temperature carbonization to obtain a spherical boron nitride @ ZIFs-derived carbon nanotube heterostructure material. The thermal conductivity of the composite material can be effectively improved by constructing a 3D thermal conductive network in a polymer matrix through a 3D spherical heterostructure and bridging adjacent fillers to reduce the interfacial thermal resistance. In addition, the present invention also prepares a composite material with high thermal conductivity by combining DIW printing molding with light / heat two-stage curing. The shear force of the DIW extrusion process is used to orient the filler and construct a three-dimensional thermal conductive network. We used multi-level hybrid fillers, including h-BN, C-BN@ZnCo-ZCNT, BNNS and g-C3N4, to form a dense and effective thermal conductive network.
[0125] The present invention prepares spherical C-BN@ZnCo-ZCNT heterostructure fillers with a size of about 8-15 μm through ultrasound, in-situ growth of MOFs and high-temperature calcination. This multi-level hybrid filler helps to build an efficient heat conduction channel. The thermal conductivity of the thermally conductive composite material loaded with 5wt% h-BN and 2.5wt% C-BN@ZnCo-ZCNT can reach 0.79W·m-1·K-1, showing great potential in the field of heat dissipation of electronic devices. Therefore, the boron nitride-ZIFs derived carbon nanotube heterostructure material prepared by the present invention can be used as a thermally conductive filler, which can effectively improve the thermal conductivity of the composite material.
[0126] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A spherical boron nitride@ZIFs-derived carbon nanotube heterostructure material, characterized in that: The spherical boron nitride@ZIFs-derived carbon nanotube heterostructure material is a spherical boron nitride C-BN on which ZIFs-derived carbon nanotubes are in-situ grown. The ZIFs are metal organic framework materials formed by metal Co, Zn and 2-methylimidazole, and are recorded as C-BN@ZnCo-ZCNT.
2. The method for preparing a spherical boron nitride@ZIFs-derived carbon nanotube heterostructure material according to claim 1, characterized in that: The following steps are involved: S1. Hexagonal boron nitride h-BN in Zn 2+ 、Co 2+ Ultrasonic treatment in metal ion solution, metal ion intercalation assisted exfoliation of h-BN to obtain spherical boron nitride C-BN, S2, adding 2-methylimidazole in situ to the mixed solution obtained in step S1, growing ZIFs particles in situ on the surface of C-BN, and obtaining a C-BN@ZIF precursor. S3, the C-BN@ZIF precursor is ground and mixed with melamine, and then calcined to in-situ grow ZIFs-derived carbon nanotubes on the surface of C-BN to obtain a spherical boron nitride-ZIFs-derived carbon nanotube heterostructure material C-BN@ZnCo-ZCNT.
3. The method according to claim 2, characterized in that In step S3, the mass ratio of C-BN@ZIF to melamine is 1:(0.1-10); preferably 1:(0.5-5), more preferably 1:(0.5-2.5), and more preferably 1:(1.0-2.5).
4. The method according to claim 2, characterized in that: In step S1, the amount of metal ions used is 3-10 mmol / g h-BN, preferably 4.5 mmol / g h-BN, and / or Preferably, the molar ratio of the metal ion in step S1 to the 2-methylimidazole in step S2 is 1:(2-80).
5. The method according to claim 2, characterized in that: In step S1, the Zn 2+ 、Co 2+ Zn in metal ion solution 2+ With Co 2+ The molar ratio is (0.1-10):(10-0.1), and / or Preferably, the Zn 2+ 、Co 2+ The metal ion solution includes at least one of nitrate solution, acetate, chloride, and / or Preferably, the Zn 2+ 、Co 2+ The solvent of the metal ion solution is a mixed solution of isopropanol and water, and the volume ratio of isopropanol to water is (1-10):(10-1).
6. The method according to claim 5, characterized in that In step S1, the ultrasonic treatment refers to 100-400W ultrasonic treatment for 2-10h; and / or Preferably, in step S3, the calcination is carried out under a nitrogen atmosphere at 700-900° C. for 2-5 hours, with a heating rate of 2-10° C. / min.
7. Application of a spherical boron nitride @ ZIFs-derived carbon nanotube heterostructure material, characterized in that: The spherical boron nitride@ZIFs-derived carbon nanotube heterostructure material is the spherical boron nitride@ZIFs-derived carbon nanotube heterostructure material according to claim 1, and is used in the fields of electronic devices, thermal conductive fillers or thermal interface materials.
8. A thermally conductive composite material, characterized in that: The thermal conductive composite material is loaded with 5wt% h-BN and 0.5-2.5wt% C-BN@ZnCo-ZCNT, and the C-BN@ZnCo-ZCNT is the spherical boron nitride@ZIFs-derived carbon nanotube heterostructure material according to claim 1.
9. The thermally conductive composite material according to claim 8, characterized in that: The thermal conductivity of the thermally conductive composite material is higher than 0.35 W·m-1·K-1; and / or Preferably, the thermal conductivity of the thermally conductive composite material is 0.79 W·m -1 ·K -1 ; and / or Preferably, the thermal conductivity of the thermally conductive composite material is 0.35-0.8 W·m -1 ·K -1 .
10. Use of the thermally conductive composite material according to claim 8 or 9 in electronic devices, thermally conductive fillers or thermal interface materials.